Computational linguistics : an international handbook on computer oriented language research and applications - Bátori, István S., 1935-; Lenders, Winfried, 1943-; Putschke, Wolfgang, 1937- (Handbücher zur Sprach- und Kommunikationswissenschaft ;, 1989)
It was the late co-editor of the series "Handbücher zur Sprach- und Kommunikationswissenschaft", Gerold Ungeheuer, who was first to recognize the need for this handbook, and who committed himself to the all important inclusion in the series. The editors dedicate this volume to his memory.